2022
DOI: 10.1177/17474930221090133
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the symptom presentation of stroke: A systematic review and meta-analysis

Abstract: Background: Early diagnosis through symptom recognition is vital in the management of acute stroke. However, women who experience stroke are more likely than men to be initially given a nonstroke diagnosis and it is unclear if potential sex differences in presenting symptoms increase the risk of delayed or missed stroke diagnosis. Aims: To quantify sex differences in the symptom presentation of stroke and assess whether these differences are associated with a delayed or missed diagnosis. Methods: PubMed, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…The meta-analysis by Shajahan et al 20 also identified motor and speech deficits as the most frequent presenting symptoms in both sexes, with no differences between women and men. However, other findings varied between the 2 meta-analyses; for example, dysarthria was more frequent and paresis less frequent in women in the analysis by Ali et al, but the opposite was found in the analysis by Shajahan et al 20 Differences in study inclusion criteria likely explain some of the discrepant findings, but the authors also emphasize that a lack of consistency in the collection and classification of symptoms in existing databases hampers our ability to evaluate potential sex differences in presentation and make a case for the use of standardized measures for data collection in future studies. Other limitations of both meta-analyses include heterogeneous populations and variable methodological quality in the included studies, the limited information on potential explanatory factors such as age, and the potential for sex-based diagnostic biases where women with minor symptoms may be less likely to undergo the advanced imaging required to be included in a study of people with confirmed stroke or transient ischemic attack events.…”
Section: Do Women Have Stroke Symptoms That Differ From Men At Presen...mentioning
confidence: 98%
See 2 more Smart Citations
“…The meta-analysis by Shajahan et al 20 also identified motor and speech deficits as the most frequent presenting symptoms in both sexes, with no differences between women and men. However, other findings varied between the 2 meta-analyses; for example, dysarthria was more frequent and paresis less frequent in women in the analysis by Ali et al, but the opposite was found in the analysis by Shajahan et al 20 Differences in study inclusion criteria likely explain some of the discrepant findings, but the authors also emphasize that a lack of consistency in the collection and classification of symptoms in existing databases hampers our ability to evaluate potential sex differences in presentation and make a case for the use of standardized measures for data collection in future studies. Other limitations of both meta-analyses include heterogeneous populations and variable methodological quality in the included studies, the limited information on potential explanatory factors such as age, and the potential for sex-based diagnostic biases where women with minor symptoms may be less likely to undergo the advanced imaging required to be included in a study of people with confirmed stroke or transient ischemic attack events.…”
Section: Do Women Have Stroke Symptoms That Differ From Men At Presen...mentioning
confidence: 98%
“…This year, 2 new meta-analyses were published with the goal of quantifying the frequency of different presenting symptoms in women and men with stroke or transient ischemic attack. 19,20 Both studies found that women were more likely than men to present with altered level of consciousness, mental status changes, and headache. The meta-analysis by Shajahan et al 20 also identified motor and speech deficits as the most frequent presenting symptoms in both sexes, with no differences between women and men.…”
Section: Do Women Have Stroke Symptoms That Differ From Men At Presen...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 To understand this area more fully, Shajahan and colleagues performed a systematic review and meta-analysis of sex differences in symptom presentation, which is published in this issue. 10 They pooled results from 21 studies in 36,636 patients with stroke, comprising 17,143 women and 19,493 men. While the prevalence of the more common neurological symptoms, such as motor and speech deficits, was similar between women and men, sex differences did exist.…”
mentioning
confidence: 99%
“…In the report by Wang and colleagues in this issue of the MJA , women subsequently diagnosed in hospital with stroke were more likely than men to be assessed by paramedics as having anxiety, nausea, headache, or being unconscious, rather than stroke 1 . Two recent meta‐analyses similarly found that women with stroke exhibit non‐focal symptoms more often than men, including generalised weakness, change in mental status, confusion, headache, and loss of consciousness 2,3 …”
mentioning
confidence: 99%